Can the Childhood Physical Activity Questionnaire Be Used to Identify Physical Activity Levels in Children With Asthma? - van der Kamp, Mattienne R.; Nieuwdorp, Bram W.; Thio, Boony J.; Tabak, Monique; Kamps, Arvid W. A.; Hermens, Hermie J.; Driessen, Jean M. M. (Frontiers in Pediatrics, 2021)
Objective: Children with asthma who are physically active have a better quality of life, emphasizing the importance of activity monitoring and promotion in daily life. The validity of self-reported activity measurements has been questioned in pediatric populations. In this study, we aim to compare the physical activity questionnaire for children (PAQ-C) with objectively measured PA using accelerometry. Design: In this comparison study the pooled dataset of two cross-sectional studies were used which prospectively home-monitored PA using the alternative self-report PAQ-C questionnaire as well as with the criterion standard accelerometry (Actigraph wGT3X-BT and GT1M). Participants: 90 children with pediatrician-diagnosed asthma (4-18y) participated in the study. Main Outcome Measures: Correlation coefficients were calculated to determine the relation between the PAQ-C and accelerometer data. The predictive value of the PAQ-C in differentiating between achieving and failing the recommended daily level of moderate-to-vigorous activity (MVPA) was evaluated with Receiver Operator Characteristic (ROC) analysis. Results: The results showed weak to moderate correlations of the PAQ-C with the accelerometer data (r=0.29 – 0.47). A PAQ-C cut-off of 3.09 showed the best performance on predicting whether the recommended level of MVPA was achieved. With this cut-off, 21 of the 39 children that did achieve their daily MVPA level (53.8% sensitivity) and 33 of the 46 children that did fail their daily MVPA level (71.7% specificity) were correctly classified. A PAQ-C score of 3.5 revealed a negative predictive value of 100% for assessing inactivity. Conclusion: This study revealed a weak relations between the PAQ-C and PA assessed with accelerometry. However, a PAQ-C score of 3.5 or higher might be used as a low cost and easy to use PA screening tool for ruling out inactivity in a portion of the pediatric asthma population.